Dynamics of emigration : émigré scholars and the production of historical knowledge in the 20th century - Berger, Stefan; Müller, Philipp (Historian), 1974- (Berghahn Books, 2022)
"As a pioneering volume to consider the impact of exile on historical scholarship in the twentieth century in a systematic and global way, looking at Europe, North America, South America and Asia, Dynamics of Emigration asks about epistemic repercussions on the experience of exile and exiles. Analyzing both the impact that exile scholars had on their host societies and on the societies they had to leave, the volume investigates exiles' pathways to integration into new host societies and the many difficulties they face establishing themselves in new surroundings. Focusing on the age of extremes and the realms of exile from fascist and right-wing dictatorships as well as communist regimes, the contributions look at the reasons scholars have for going into exile while providing side-by-side examination of the support organizations and paths for success involved with living in exile"-- Provided by publisher.
Keywords: Historiography -- History -- 20th century.; Historians.; Exiled scholars -- History -- 20th century.; Learning and scholarship -- History -- 20th century.; Historiographie -- Histoire -- 20e siècle.; Savoir et érudition -- Histoire -- 20e siècle.; HISTORY / Modern / 20th Century.; HISTORY / Modern / 20th Century / General; Exiled scholars; Historians; Historiography; Learning and scholarship; 1900-1999; History